Diverse NPMM conditions deviate the 2023/24 El Niño from the 1997/1998 and 2015/2016 extreme El Niño events - Yong-Fu Lin; Mengyan Chen; Lingling Liu; Fei Zheng; Ruiqiang Ding; Xin Wang; Chau-Ron Wu; Min-Hui Lo; Huang-Hsiung Hsu; Jiepeng Chen; Ting-Hui Lee; Jin-Yi Yu (npj Climate and Atmospheric Science)
Abstract The 2023/24 El Niño commenced with an exceptionally large warm water volume in the equatorial western Pacific, comparable to the extreme 1997/98 and 2015/16 events, but did not develop into a super El Niño. This study highlights the critical role of contrasting Northern Pacific Meridional Mode (NPMM) conditions in this divergence. Warm NPMM conditions during the 1997/98 and 2015/16 events created a positive zonal sea surface temperature (SST) gradient in the equatorial western-central Pacific and enhanced Madden-Julian Oscillation (MJO) propagation, driving sustained westerly wind bursts (WWBs) and downwelling Kelvin waves that intensified both events. In contrast, the cold NPMM during 2023/24 induced a negative SST gradient and suppressed MJO activity, resulting in weaker WWBs and limited eastward wave activity, preventing the event from reaching super El Niño intensity. A 2,200-year CESM1 pre-industrial simulation corroborates these observational findings, underscoring the importance of NPMM interference in improving El Niño intensity predictions.